Communication Relationship of The Radiographer with The Patient Satisfaction Information Service in Radiological Facilities - Hidayati, Alpha Olivia; Jemamun, Agustina Erfianita; Arifah, Siti (Universitas Nusa Cendana, 2023)
Providing satisfactory health services is a demand for hospitals, including radiology installations at the Bagas Waras Hospital, Klaten, Central Java. Effective communication is one of the significant factors affecting the quality of service to patients. The purpose of this study was to determine the relationship between radiographer's communication and satisfaction with information services for patients in terms of respect, empathy, audible, clarity, and humble indicators. This type of research is a quantitative analytical observational study with a cross sectional design. The sample size in this study was 193 samples taken by purposive sampling. Data collection was carried out using a questionnaire that had been tested for validity and reliability, then the data obtained were tested by univariate and bivariate (Chi Square) tests. The results showed that the p-value between the radiographer's communication and satisfaction with information services for patients on the indicators of respect, empathy, audible, clarity, and humble with a value of 0.000 <0.05. When viewed from the PR value for each indicator, it is 23,429 times for the respect indicator; 15,385 times on audible indicators; 20 times on the empathy indicator; 16,902 times on the clarity indicator and 39 times on the humble indicator. The conclusion of this study is that there is a relationship between radiographer's communication and information service satisfaction for patients at the Bagas Waras Hospital, Klaten, Central Java, both on the indicators of respect, empathy, audible, clarity, and humble. The advice that can be given based on this research is the need to improve the communication skills of radiographers through training.